Thematization in Native and Nonnative Medical Discourse: A Systemic Functional Approach - ALRAJHI, MASHAEL (International Journal of Language and Literary Studies, 2020)
Thematization serves to focus the readers’ attention to the focal aspects of a text in order to deliver its intended interpretation. The cohesion of texts relies on the structure of messages. Consequently, the way in which messages are constructed as the text unfolds contributes to its cohesion. Since the probability of making mistakes in writing is higher in nonnative texts as their writers are not using their mother tongue, a comparison between medical articles written by native and nonnative writers is drawn in the present study to shed light on the similarities and differences among them. Due to the scientific nature of medical texts, writers might face difficulties in the interconnectedness of ideas within the text. Therefore, the medical field texts are inspected to check their correspondence with texts in other fields. The Hallidayan systemic-functional approach (SFL) was utilized to conduct the analysis. The results show that there is a consistency in the distribution of Theme types and Thematic progression patterns among native and nonnative writers. In addition, the findings that relate to the dominance of the topical Theme and the constant Theme pattern in medical texts are in alignment with the results of studies in other fields such as academia.